Isotopic Data on Diet and Mobility from Pictish and Viking Age Orkney - Alexandra Johnson; Christophe Snoeck; Rick Schulting; Philippe Claeys; Nadine Mattielli; Gail Drinkall (Journal of Open Archaeology Data)
Changes in diet and mobility isotopes from the Late Iron Age or Pre-Viking phase (PVP, AD 550–790) through the Viking Age (VA, AD 790–1050) and Late Norse phase (LNP, AD 1050–1300) can be used to suggest nuanced socioeconomic and political change, including differences in subsistence practices and social constructs of ethnicity, religion and status [1234567]. We present here isotopic analysis on some 292 individuals from 10 sites across Orkney, including 152 individuals newly analysed for δ13C and δ15N from bone collagen and 54 individuals analysed for δ18O and 87Sr/86Sr from tooth enamel, in addition to data from previous studies. In addition to the human remains, 29 plant samples were collected to supplement the geological baseline for strontium isotopes. This study provides new results as evidence of increased δ13C and δ15N at the end of the first millennium, with dietary differences between ‘local’ and ‘non-local’ individuals.